Loss of the small GTPase Arl8b results in abnormal development of the roof plate in mouse embryos. (26th May 2019) - Hashimoto, Keisuke; Yamaguchi, Yoshifumi; Kishi, Yusuke; Kikko, Yorifumi; Takasaki, Kanako; Maeda, Yurie; Matsumoto, Yudai; Oka, Miho; Miura, Masayuki; Ohata, Shinya; Katada, Toshiaki; Kontani, Kenji
Abstract: Lysosomes are acidic organelles responsible for degrading both exogenous and endogenous materials. The small GTPase Arl8 localizes primarily to lysosomes and is involved in lysosomal function. In the present study, using Arl8b gene‐trapped mutant ( Arl8b −/− ) mice, we show that Arl8b is required for the development of dorsal structures of the neural tube, including the thalamus and hippocampus. In embryonic day (E) 10.5 Arl8b −/− embryos, Sox1 (a neuroepithelium marker) was ectopically expressed in the roof plate, whereas the expression of Gdf7 and Msx1 (roof plate markers) was reduced in the dorsal midline of the midbrain. Ectopic expression of Sox1 in Arl8b −/− embryos was detected also at E9.0 in the neural fold, which gives rise to the roof plate. In addition, the levels of Bmp receptor IA and phosphorylated Smad 1/5/8 (downstream of BMP signaling) were increased in the neural fold of E9.0 Arl8b −/− embryos. These results suggest that Arl8b is involved in the development of the neural fold and the subsequently formed roof plate, possibly via control of BMP signaling. Abstract : The small GTPase Arl8b is required for normal brain development. Loss of Arl8b leads to abnormal development of the neural fold and the roof plate in mouse embryos.